Digital Drama Technique in English as a Foreign Language Teaching and Learning: From Viewers’ and Actors’ Perspectives - Thao, Le Thanh; Yen, Phuong Hoang; Khang, Nguyen Duy; Khoi, Vuong Tan Minh; Quyen, Bui Nha (Nurture, 2022)
Purpose: Due to the emergence of COVID -19, the transition from offline to online teaching also changes how drama techniques work. Specifically, the digital drama technique was used to teach English, when regular classes were almost impossible. There seems to be very little, if any, research on digital drama techniques, especially in the Vietnamese context. Consequently, this study examines how the digital drama technique affects Vietnamese students learning English as a foreign language (EFL). Additionally, the differences and similarities between teachers’ and students’ perceptions of the technique’s impact are examined. Methodology: The study used a quantitative approach. A survey was used to collect data from 1207 students and 69 teachers. Findings: The survey revealed that the technique was helpful for EFL students’ learning. The participants mostly perceived the positive impacts of the technique. However, differences in perception between teacher and student were discovered. The students considered it beneficial for improving their writing and reading skills while teachers perceived this technique as helpful in exploring new creative ideas. Practical implications: The technique was approved as useful for language teaching and learning. English teachers are encouraged to use this technique in their teaching in practice. Contribution to literature: The study becomes a good source for further research to build a more profound theoretical framework. More researchable ideas related to this unique online teaching technique are suggested to enrich the literature in this field.